Liquid sourdough from stone-ground soft wheat (Triticum aestivum) flour: Development and exploitation in the breadmaking process. (November 2022) - Cardinali, Federica; Garofalo, Cristiana; Reale, Anna; Boscaino, Floriana; Osimani, Andrea; Milanović, Vesna; Taccari, Manuela; Aquilanti, Lucia
Graphical abstract: Highlights: Setup of a stone-ground wheat Type II sourdough for the breadmaking process. Chemical and microbiological features of stone-ground wheat sourdoughs were tested. Type II sourdough fermentation affects the aroma profile of the final products. The sensory properties of stone-ground wheat bread have been described. Abstract: The aim of the study was to set up a liquid sourdough obtained using stone-ground soft wheat ( Triticum aestivum ) flour to be exploited in breadmaking. Therefore, a Type II sourdough (dough yield = 350) was developed from a stable stone-ground wheat Type I sourdough (dough yield = 156) used as inoculum. Both sourdoughs were analyzed for lactic acid bacteria (LAB) viable counts, pH and total titratable acidity (TTA), LAB biodiversity by a combined culture-dependent and -independent approach (PCR-DGGE) and they were tested for their breadmaking ability. In addition, the chemical and rheological features and volatile organic compounds of the stone-ground soft wheat flour used in the experiment were investigated. The flour had a high protein content, good bakery properties and it also presented a rich aroma pattern characterized not only by the prevalence of green grass, flowery, and sweet aromas but also nutty, roasted and popcorn aromas. The sourdoughs I and II used in the trial were characterized by viable LAB counts, pH and TTA values typical of mature sourdoughs, i.e., approximately 9 log cfu gr -1 and mL, pH 3.9 and 10 mL 0.1 N NaOH. In addition, Levilactobacillus brevis and Companilactobacillus paralimentarius species represented the LAB stable microbiota of both sourdoughs. Both sourdoughs efficiently produce acceptable experimental breads characterized by different volatile profiles thus indicating that the type of sourdough fermentation significantly influenced the features of the final products. Overall, for the first time in the present study stone-ground wheat flour and bread have been characterized for their volatile aroma profile and sensory properties.